Myasthenia gravis and endurance exercise - Scheer, Bernd Volker; Valero-Burgos, Encarna; Costa, Ricardo (American journal of physical medicine & rehabilitation, 2012)
ABSTRACT This is the first report of a runner with myasthenia gravis who completed an ultra endurance event. Myasthenia gravis, a neuromuscular disease that usually results in skeletal muscle weakness, which worsens with exercise and strenuous aerobic exercise, is generally contraindicated. Our runner completed a 220-km, 5-day ultramarathon and presented with various symptoms including muscular skeletal weakness, cramps, generalized fatigue, unintelligible speech, involuntary eye and mouth movements, problems swallowing, food lodging in his throat, and problems breathing. Risk factors identified for exacerbations are running in extreme temperatures, prolonged runs (especially a distance of 30 km or more), running uphill, lack of sleep, and stress. The medical team was in the novel situation to look after a runner with myasthenia gravis and needed to be aware of the patient’s condition, symptoms, and risk factors to safely care for him.